SECURITY THREATS IN IOT TECHNOLOGIES - Vasiyeva , Dilfuza (Educational Research in Universal Sciences, 2023)
IoT technology is one of the key issues that need to be addressed. There are various configurations of issues that need to be addressed in the physically connected part of the IoT and in the network domain. IoT automation programs have special requirements in real time, they have a high level of reliability and security in a stable environment. These requirements strengthen security and high security measures. This article discusses security threats that may arise in various layers of iot architecture, especially in the automation domain. Impact mitigation methods are discussed with security in mind, with equipment in the field, communication infrastructure resulting in a variety of physical solutions and measurements for data processing applications.